Contending with Antisemitism in a Rapidly Changing Political Climate - Rosenfeld, Alvin H. (Alvin Hirsch), 1938- (Book collections on Project MUSE., 2021)
"Today's highly fraught historical moment brings a resurgence of antisemitism. Antisemitic incidents of all kinds are on the rise across the world, including hate speech, the spread of neo-Nazi graffiti and other forms of verbal and written threats, the defacement of synagogues and Jewish cemeteries, and acts of murderous terror. Contending with Antisemitism in a Rapidly Changing Political Climate is an edited collection of 18 essays that address antisemitism in its new and resurgent forms. Against a backdrop of concerning political developments such as rising nationalism and illiberalism on the right, new forms of intolerance and anti-liberal movements on the left, and militant deeds and demands by Islamic extremists, the contributors to this timely and necessary volume seek to better understand and effectively contend with today's antisemitism"--